Peran kepuasan kerja memediasi pengaruh kepemimpinan transformasional terhadap kinerja karyawan - Adipra, I Made Yoga; Surya, Ida Bagus Ketut (Universitas Negeri Surabaya, 2025)
The role of job satisfaction as a mediator in the relationship between transformational leadership and employee performance is essential, especially given the intensifying competition in today's business environment. In this era of globalization, companies are not only expected to operate efficiently but also to identify and enhance factors that boost productivity and competitiveness. This research was conducted at PT. X, involving a sample of 88 employees selected through purposive sampling. Data were gathered via questionnaires and analyzed using path analysis techniques with SPSS. The study aims to examine the mediating role of job satisfaction in the impact of transformational leadership on employee performance. The findings reveal that both transformational leadership and job satisfaction significantly influence employee performance in a positive direction, with transformational leadership also positively affecting job satisfaction. However, job satisfaction does not mediate the relationship between transformational leadership and employee performance. The implications of this study are primarily theoretical, as the results challenge the conventional perspective of Herzberg's theory, which posits that job satisfaction is the primary mediator between motivational factors and performance, by demonstrating that transformational leadership can directly influence employee performance through a more complex mechanism.